Autoimmunity to neuronal nicotinic acetylcholine receptors - Pechlivanidou, Maria; Ninou, Elpinickie; Karagiorgou, Katerina; Tsantila, Aikaterini; Mantegazza, Renato; Francesca, Andreetta; Furlan, Raffaello; Dudeck, Leon; Steiner, Johann; Tzartos, John; Tzartos, Socrates (Pharmacological research, 2023)
Nicotinic acetylcholine receptors (nAChRs) are widely expressed in many and diverse cell types, participating in various functions of cells, tissues and systems. In this review, we focus on the autoimmunity against neuronal nAChRs, the specific autoantibodies and their mechanisms of pathological action in selected autoimmune diseases. We summarize the current relevant knowledge from human diseases as well as from experimental models of autoimmune neurological disorders related to antibodies against neuronal nAChR subunits. Despite the well-studied high immunogenicity of the muscle nAChRs where autoantibodies are the main pathogen of myasthenia gravis, autoimmunity to neuronal nAChRs seems infrequent, except for the autoantibodies to the ganglionic receptor, the α3 subunit containing nAChR (α3-nAChR), which are detected and are likely pathogenic in Autoimmune Autonomic Ganglionopathy (AAG). We describe the detection, presence and function of these antibodies and especially the recent development of a cell-based assay (CBA) which, contrary to until recently available assays, is highly specific for AAG. Rare reports of autoantibodies to the other neuronal nAChR subtypes include a few cases of antibodies to α7 and/or α4β2 nAChRs in Rasmussen encephalitis, schizophrenia, autoimmune meningoencephalomyelitis, and in some myasthenia gravis patients with concurrent CNS symptoms. Neuronal-type nAChRs are also present in several non-excitable tissues, however the presence and possible role of antibodies against them needs further verification. It is likely that the future development of more sensitive and disease-specific assays would reveal that neuronal nAChR autoantibodies are much more frequent and may explain the mechanisms of some seronegative autoimmune diseases. [Display omitted]